Free Radicals and Antioxidants in Crabs - Srimeetian, Pattarawadee (Journal of Mahanakorn Veterinary Medicine, 2021)
Free radicals can cause damage biomolecule of crab cells such as DNA, RNA, proteins and lipids. Superoxide anion (O2=-) hydroxyl (=OH) and hydrogen peroxide (H2O2) are some of free radicals. The occurrence of free radicals in crabs are produced in process of metabolism (such as respiration and molt cycle). Moreover, the free radicals are produced in the processes to eliminate the pathogens and xenobiotic (such as bacteria, virus, cyanobacteria and heavy metals). Free radicals are inhibited by antioxidants such as superoxide dismutase, catalase, glutathione peroxidase and glutathione.